Organizational behavior : concepts, conhtroversies, applications - Robbins, Stephen P. (New Delhi : Prentice-Hall of India, 1998)
Business
Keywords: Organizational behavior; Decision making; Job satisfaction; Motivation; Communication; Leadership; Organization structure; Work design; Human resource policies